New species of Protosticta Selys from Vietnam with a key to the males of the P. curiosa group (Odonata: Platystictidae) - Kompier, Tom (Zootaxa, 2016)
Three new species of Protosticta Selys, 1855, are described from Vietnam: P. proboscis spec. nov. and P. albifrons spec. nov., while P. satoi dark form is elevated to specific status as P. nigra spec. nov. based on structural and morphological differences. The female of P. linnaei is described for the first time and a key provided to the males of the P. curiosa group in Vietnam.